Books in the Catholic world during the early modern period - Maillard Alvarez, Natalia (Library of the written word, 2014)
The current volume aims to shed new light on the relationships between Catholicism and books during the early modern period, gathering studies with special focus on trade, common readings and the mechanisms used to control readership in different territories.